2021
DOI: 10.1371/journal.pone.0245651
|View full text |Cite
|
Sign up to set email alerts
|

Finding uncommon ground: Extremist online forum engagement predicts integrative complexity

Abstract: How do interactions with an ideologically extreme online community affect cognition? In this paper, we examine whether engagement with an online neo-Nazi forum is associated with more one-sided, “black and white” thinking. Using naturalistic language data, we examined differences in integrative complexity, a measure of the degree to which people acknowledge and reconcile conflicting ideas and viewpoints, and contrasted it with Language Style Matching, a measure of group cohesion. In a large web scraping study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Such spatial formations are found within the online world through online groups and communities that may contribute to group-think or ideological polarisation. Analysing scraped data from a white supremacist online forum, Stormfront.org, Gregory and Piff [ 56 ] found that both cognitive complexity and style matching decreased as engagement increased, indicating increased ideological polarisation during ongoing engagement rather than the deindividuation that characterises groupthink. Studying online video games, Robinson and Whittaker [ 57 ] argue that interactive gameplay and the use of iconography such as Nazi memorabilia creates conditions of belonging that can include adherence to extremist ideologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such spatial formations are found within the online world through online groups and communities that may contribute to group-think or ideological polarisation. Analysing scraped data from a white supremacist online forum, Stormfront.org, Gregory and Piff [ 56 ] found that both cognitive complexity and style matching decreased as engagement increased, indicating increased ideological polarisation during ongoing engagement rather than the deindividuation that characterises groupthink. Studying online video games, Robinson and Whittaker [ 57 ] argue that interactive gameplay and the use of iconography such as Nazi memorabilia creates conditions of belonging that can include adherence to extremist ideologies.…”
Section: Discussionmentioning
confidence: 99%
“…The literature both within this review and otherwise (see, e.g., [ 17 ]) identified social media, peer-to-peer, video hosting and collaborative platforms as conduits to extremist material. And there appears to be a growing number of radicalised individuals amongst younger users of short-attention video platforms, such as Tik Tok, gaming platforms, including Twitch, or online videogames [ 56 ]. Tik Tok, for example, is notable for its lack of enforcement around community guidelines and has been implicated in the rise of alt-right sentiment amongst young people [ 17 ] alongside Islamist content accessed by different young populations [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…As of January 2023, a search of the keyword “web scraping” in Medline yielded 105 records, 95 of which were published starting from 2019. Articles using web scraping in health and social research mostly used information from social media [ 13 , 14 ] (eg, Twitter, Instagram, and TikTok), forums [ 15 , 16 ], business and review websites [ 17 ], and news web pages [ 18 ].…”
Section: Introductionmentioning
confidence: 99%